DEMOCRACY: IS IT NECESSARY? - Mudiyati Rahmatunnisa (Universitas Padjadjaran, 2003)
There is a great resistance from several Asian country leaders towards democracy. Basically, they view that the US has “forced” some Asian countries to implement its model of government which is thought to be a good form of government for all countries, particularly in terms of placing democracy as a “yardstick” when some of the countries need International Aids. While actually, they argue that what works for one country does not necessarily appropriate for others. Lee Kuan Yew argue that what people’s real need is a “good government”, whase its implementation might differ for each country and might also differ from “Western” values. Nevertheless, some observers have criticized the concept as well. They argue that it has been implemented on the expense of restricting political space available for he citizens. This essay will elaborate each of the claims and will try to provide a tentative alternative which might need further discussion. Keywords: Democracy; Good government; Western Values